2000
DOI: 10.1046/j.1468-2982.2000.00010.x
|View full text |Cite
|
Sign up to set email alerts
|

Cluster of MMPI Personality Profiles in Chronic Tension-Type Headache and Predictable Response to Fluoxetine

Abstract: A study was made of the personality profiles of a sample of 51 patients with chronic tension-type headache (CTH) employing the Minnesota Multiphasic Personality Inventory (MMPI). Two clusters were obtained by applying multivariate classification techniques: cluster 1 (with elevations on scales Hy, D and Hs only) and cluster 2 (exhibiting elevations on most scales except Pd, Mf and Si). Fifty subjects without chronic pain or known psychiatric disorders, and extracted from the same social setting as the patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 56 publications
0
11
0
2
Order By: Relevance
“…Investigations of MMPI profiles in patients with CTTH have found reliable increases in the "neurotic triad" [5,31,32]. The neurotic triad is a group of elevated scores on the MMPI's first three basic scales (ie, hypochondriasis, hysteria, and depression; Table 3).…”
Section: Mmpi-based Researchmentioning
confidence: 99%
“…Investigations of MMPI profiles in patients with CTTH have found reliable increases in the "neurotic triad" [5,31,32]. The neurotic triad is a group of elevated scores on the MMPI's first three basic scales (ie, hypochondriasis, hysteria, and depression; Table 3).…”
Section: Mmpi-based Researchmentioning
confidence: 99%
“…[2][3][4][5][8][9][10][11][12][13] In CTTH, persistent pain has been claimed to be related to underlying psychological pathology or personality disorders. 14 Early studies of personality in patients with headache used the Minnesota Multiphasic Personality Inventory (MMPI) to distinguish between physiologic pain and psychogenic pain and to predict treatment outcome [15][16][17][18] Most studies have found a conversion V (clinical elevations on scales that measure hypochondriasis, depression and hysteria) in CTTH, thus indicating that certain personality traits participate in the formation of headaches by increasing the vulnerability of a person to suffer headaches.…”
Section: Introductionmentioning
confidence: 99%
“…Los síntomas de ansiedad y depresión están presentes tanto en las migrañas crónicas (80%) como en las cefaleas tensionales crónicas (90%) [28][29][30][31][32][33]. También es frecuente la presencia de un perfil psicopatológico más alterado, evaluado con el MMPI-2 [34][35][36][37] o con el SCL-90-R [38] respecto a los controles sin cefalea.…”
Section: Discussionunclassified